A novel multi-resonant and wideband fractal antenna for telecommunication applications - Ibrahime Hassan Nejdi; Youssef Rhazi; Mustapha Ait Lafkih; Seddik Bri; Lamsalli Mohammed (Institute of Advanced Engineering and Science, 2022)
This letter presents the design, simulation, and measurement of a novel multiband fractal circular antenna for wireless applications. In the antenna design, we used a circular antenna where we took a ring. Then, in the first iteration, we added a new ring divided into two of the same size. For the second iteration, we added a ring of the same size after dividing it into two halves. In the third iteration, we added the third ring of the same size after dividing it into four. Due to the resonator defection, we were able to reduce the size of the starting antenna from 60×70×2 mm3 to 50×50×1.6 mm3, to get the frequency of 2.48 GHz, and we generated new bandwidths with a high gain that reaches 5.02 dB. The proposed antenna radiation characteristics, such as the impedance matching, the gain, the radiation pattern, and the surface current distribution are presented and discussed. We find that the simulated and measured results are in acceptable agreement and affirm the good performance of the proposed antenna. The results obtained affirm that the proposed fractal antenna is a better candidate for integration into wireless communication circuits.